P005 Competitive fitness and trade-offs associated with azole resistance in Candida auris clinical isolates. (20th September 2022) - Das, Sourav; Tawde, Yamini; Singh, Shreya; Chakrabarti, Arunaloke; Rudramurthy, Shivaprakash M; Kaur, Harsimran; Shaw, Tushar; Ghosh, Anup
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Objectives: Following the global emergence of Candida auris, this multidrug-resistant yeast has become a concern of serious threat to public health. The evolution of such multidrug-resistant pathogens depends on their relative fitness to their susceptible counterparts. Fitness cost, expressed in terms of reduced competitive ability of survival in the absence of drugs, plays a key role in the drug resistance dynamics. The objectives of the study were to investigate the oxidative stress response (OSR) in fluconazole-resistant C. auris and to compare its relative fitness with fluconazole-susceptible strains. Methods: A total of 351 C. auris clinical isolates (61 flu-susceptible and 290 flu-resistant) were screened for stress tolerance by spot assay on yeast-peptone-dextrose (YPD) agar containing 5-50 mm H2O2 (with 5 mm increments) and results were rechecked on YPD broth. Expressions of Hog1, Cta1, Sod1, Mkc1, Cek1, Calcineurin1 genes were evaluated under oxidative stress by qPCR. Cellular catalase level was determined by colorimetric catalase assay kit (EnzyChrom, Bioassay systems). DHR-123 assay was performed to measure the intracellular reactive oxygen species level (iROS) under H2O2 exposure. Adherence, biofilm formation and XTT [2, 3-Bis-(2-Methoxy-4-Nitro-5-Sulfophenyl)-2H-Tetrazolium-%-Carboxanilide] cell viability were estimated under hyper-oxidative stress condition. C. auris were co-cultured with human neutrophils from healthy donors and the percentage of fungal killing was recorded. Scanning electron microscopy (SEM) images were taken to check the cellular association under increasing H2O2 exposure. Results: A total of 95.08% (58/61) flu-susceptible isolates were hyper-resistant to oxidative stress (30-50 mm ) while 94.5% (274/290) flu-resistant isolates showed lower tolerance to oxidative stress (10-25 mm ). Hog1 ( P = .0012) and Cta1 ( P = .01) transcript levels were highly elevated in flu-susceptible isolates when exposed to 10 mm of H2O2 while no significant difference was observed in resistant isolates. Flu-susceptible isolates exhibited a higher level of catalase ( P = .002) compared with resistant isolates upon 10 mm H2O2 exposure. Owing to the reduced catalase activity, a higher iROS level was accumulated in resistant isolates. Flu-susceptible isolates formed higher biofilms at 37°C both under no-stress (control, P <.001) and hyper-oxidative condition (10 mm, P = .002). At 42°C, there was a significant reduction in biofilm among resistant isolates under 10 mm H2O2 compared to no-stress control (from mean OD 0.48 ± 0.26 to 0.23 ± 0.09) ( P = .02). Susceptible isolates had better adherence capacity even at 42°C both under no-stress (control, P = .01) and under 15 mm H2O2 exposure ( P <.001). Higher fungal killing was achieved in Flu-resistant isolates when co-cultured with human neutrophils ( P = .014) compared to susceptible counterparts. Conclusion: Collectively, these data revealed that in C. auris, resistance to fluconazole is accompanied by fitness trade-offs. Fluconazole-resistant C. auris strains have diminished ability to survive the diverse array of stresses that are encountered in a mammalian host and reduced virulence traits essential for invasive disease.